Peningkatan Peran Serta Ibu-Ibu dalam Rumah Tangga Melalui Pelatihan Pendidikan Karakter dan Keterampilan Membuat Makanan Jajanan Berbasis Bahan Lokal - Setiawati Setiawati; Syuraini Syuraini (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2018)
Women's participation in this case is housewives in supporting the family economy and children's education is currently very much needed. This is due to the increasing demands and needs of life today. In addition, if observed today, there has been a decline in the moral behavior of children and adolescents today, requiring serious handling by the family. The same thing was felt by the people of Lubuk Jantan, Lintau Buo Subdistrict, this problem was allegedly caused by the low understanding and skills of mothers about the character education and productive economic stability they had. This community service activity aims to enable housewives to (1) have skills in making cheap, lively, quality (3M) snacks based on local ingredients. (2) For young mothers to have motivation in enterpreneurship. (3) For young mothers to have the ability to market the results of their businesses. (4) For housewives to be able to shape their children's character towards a better direction. The target of this service is housewives in the Lubuk Jantan region, totaling 20 people. The results obtained from this service are, as a whole, the housewives who have been programmed already have some skills in making cheap, lively, quality snacks from local ingredients such as: from sea fish, from cassava, from white rice and glutinous rice, from flour and various kinds of pudding. In general, mothers who take part in the training have been able to instill the value of character values for children, because along with skills training, they are also given knowledge about planting character values in the family.Key Words: Training to Make Snacks, Housewives